Combined Antimicrobial Activity of Photodynamic Inactivation and Antimicrobials–State of the Art - Wozniak, Agata; Grinholc, Mariusz (Frontiers in Microbiology, 2018)
Antimicrobial photodynamic inactivation (aPDI) is a promising tool for the eradication of life-threatening pathogens with different profiles of resistance. This study presents the state-of-the-art published studies that have been dedicated to analyzing the bactericidal effects of combining aPDI and routinely applied antibiotics in in vitro (using biofilm and planktonic cultures) and in vivo experiments. Furthermore, the current paper reviews the methodology used to obtain the published data that describes the synergy between these antimicrobial approaches. The authors are convinced that the use of a unified experimental methodology that is in agreement with antimicrobial susceptibility testing (AST) is required to investigate possible synergistic cooperation between aPDI and antimicrobials. Conclusions concerning the possible synergistic activity between the two treatments can be drawn only when appropriate assays are employed.